2022
DOI: 10.1177/19322968221110830
|View full text |Cite
|
Sign up to set email alerts
|

Use of Continuous Glucose Monitors by People Without Diabetes: An Idea Whose Time Has Come?

Abstract: Background: Continuous glucose monitor (CGM) systems were originally intended only for people with diabetes. Recently, there has been interest in monitoring glucose concentrations in a variety of other situations. As data accumulate to support the use of CGM systems in additional states unrelated to diabetes, the use of CGM systems is likely to increase accordingly. Methods: PubMed and Google Scholar were searched for articles about the use of CGM in individuals without diabetes. Relevant articles that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Originally, the system was developed to improve glycaemic control in patients with diabetes, and also, the standards for interpreting the CGM readings are dedicated to this group of subjects [ 26 ]. Subsequently, the method was deployed in other clinical situations related and not related to disordered glucose metabolism (e.g., hypoglycaemia in neonates, patients in critical conditions, sport medicine, and healthy individuals) [ 27 ]. We have shown that for patients with chronic CNS damage who are tube-fed, hypoglycaemia can be a significant clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the system was developed to improve glycaemic control in patients with diabetes, and also, the standards for interpreting the CGM readings are dedicated to this group of subjects [ 26 ]. Subsequently, the method was deployed in other clinical situations related and not related to disordered glucose metabolism (e.g., hypoglycaemia in neonates, patients in critical conditions, sport medicine, and healthy individuals) [ 27 ]. We have shown that for patients with chronic CNS damage who are tube-fed, hypoglycaemia can be a significant clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…Patient adoption of CGM devices has been rapidly expanding, as evidenced by a 237% revenue increase of Dexcom between 2018−2021 and a forecasted global CGM market of $15 billion by 2032. 925 The success of CGMs has also led to the idea of assigning glucotypes in non-diabetic individuals, 926 in which people can track their glycemic responses to get more precise ideas of their predisposition to diabetes. Companies such as Levels Health and Nutrisense now sell CGMs with related software and information to those interested in monitoring their glucose responses in the context of weight loss, athletic performance, and improved general wellbeing.…”
Section: Lab To End-usermentioning
confidence: 99%
“…[1] Increased visibility of glucose data has resulted in a recent trend of individuals without DM using CGM as a means of monitoring their health. [2] One area of interest is the effect of post-prandial hyperglycemia (PPHG) upon the health of individuals with and without DM. Through dietary and lifestyle changes, individuals attempt to minimize PPHG to aid weight loss, optimize mental health, suppress hunger and food cravings, improve sleep, as well as avoid glycemic fluctuations which could lead to chronic disease including cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%